Additive cardioprotection by pharmacological postconditioning with hydrogen sulfide and nitric oxide donors in mouse heart: S-sulfhydration vs. S-nitrosylation. Issue 1 (17th February 2016) - Sun, Junhui; Aponte, Angel M.; Menazza, Sara; Gucek, Marjan; Steenbergen, Charles; Murphy, Elizabeth
Abstract: Hydrogen sulfide (H2 S), as a gaseous signalling molecule, has been found to play important roles in postconditioning (PostC)-induced cardioprotection. Similar to nitric oxide (NO)-mediated protein S-nitrosylation (SNO), recent studies suggest that H2 S could regulate protein function through another redox-based post-translational modification on protein cysteine residue(s), i.e. S-sulfhydration (SSH). In this study, we examined whether there are changes in protein SSH associated with cardioprotection induced by treatment with H2 S on reperfusion. In addition, we also examined whether there is cross talk between H2 S and NO. Compared with control, treatment on reperfusion with NaHS (H2 S donor, 100 µmol/L) significantly reduced post-ischaemic contractile dysfunction and infarct size. A comparable cardioprotective effect could be also achieved by reperfusion treatment with SNAP (NO donor, 10 µmol/L). Interestingly, simultaneous reperfusion with both donors had an additive protective effect. In addition, C-PTIO (NO scavenger, 20 µmol/L) eliminated the protection induced by NaHS and also the additive protection by SNAP + NaHS together. Using a modified biotin switch method, we observed a small increase in SSH following NaHS treatment on reperfusion. We also found that NaHS treatment on reperfusion increases SNO to a level comparable to that with SNAP treatment. In addition, there was an additive increase in SNO but not SSH when SNAP and NaHS were added together at reperfusion. Thus, part of the benefit of NaHS is an increase in SNO, and the magnitude of the protective effect is related to the magnitude of the increase in SNO.